MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DAN TANTANGANNYA (STUDI KASUS TK ISLAM TUNTANG) - Zulfiana; Noor Miyono (STKIP Subang, 2024)
The aim of this research is to find out how School-Based Quality Improvement Management works by looking at educational input, educational processes and educational output. This research was conducted at the Tuntang Islamic Kindergarten which received category